Uvod v kartiranje kriminalitete - Eman, Katja; Hacin, Rok (University of Maribor Press, 2021)
Introduction to Crime Mapping. Textbook with tutorials on mapping results from twenty years of research at the Faculty of Criminal Justice, University of Maribor. The textbook itself comprises 17 chapters, which can be divided into two parts. In the first (theoretical) part, which consists of five chapters, students are introduced to Geographic Information Systems (GIS), the history of mapping, and crime mapping development. The second part of the textbook comprises 12 tutorials, through which students will learn how to use the tools offered by the ArcGIS program in practice. Tutorials follow the difficulty level (from the first basic steps to independent work). The textbook itself is primarily intended for students of the Faculty of Criminal Justice and Security, University of Maribor, who want to get acquainted with analytics and mapping, as the emphasis is on mapping crime and other deviant phenomena. Moreover, the textbook presents useful material for practitioners in the institutions of criminal justice (especially the police) and other interested individuals.